Synergic versus Antagonist Effects of Rutin on Gallic Acid or Coumarin Incorporated into Chitosan Active Films: Impacts on Their Release Kinetics and Antioxidant Activity - Elizabeth Jacobs; Odile Chambin; Frédéric Debeaufort; Nasreddine Benbettaieb (Antioxidants, 2023)
This work deals with the study of the release and antioxidant activity kinetics of three natural antioxidants associated as binary mixture (coumarin, and/or gallic acid and rutin) from chitosan films. Antioxidants were incorporated into film alone or in binary mixture. The aim was to determine the influence of rutin on the phenolic acid and benzopyrone. The UV-visible light transmission spectra of the films were also investigated. Neat chitosan films and chitosan incorporated coumarin exhibited high transmittance in the UV-visible light range, while GA-added chitosan films showed excellent UV light barrier properties. The molecular interactions between chitosan network and antioxidants were confirmed by FTIR where spectra displayed a shift of the amide-III peak. Rutin has a complex structure that can undergo ionization. The chitosan network structure induced change was found to influence the release behavior. The film containing rutin showed the highest antioxidant activity (65.58 ± 0.26%), followed by gallic acid (44.82 ± 3.73%), while coumarin displayed the lowest activity (27.27 ± 4.04%). The kinetic rate against DPPH-free radical of rutin is three times higher than coumarin. The kinetic rates were influenced by the structure and interactions of the antioxidants with chitosan. Rutin exhibited a slow release due to its molecular interactions with chitosan, while coumarin and gallic acid showed faster release. The diffusion coefficient of coumarin is 900 times higher than that of rutin. The rutin presence significantly delayed the release of the gallic acid and coumarin, suggesting an antagonistic effect. However, their presence weakly affects the release behavior of rutin.